(NH4)2S2O8-Promoted Direct C–C Coupling of Indoles with Quinones/Hydroquinones without Catalyst - Dong, Yu; Ye, Ji-Xian; Luo, Qi-Qi; Mei, Ting; Shen, Ai; Huang, Peng; Chen, Jia; Zhang, Xia; Xie, Chun; Shi, Zhi-Chuan (Synlett, 2021)
An atom-economical and environmentally benign approach for the synthesis of 3-indolylquinones was achieved successfully via direct oxidative C–C coupling of quinones/hydroquinones with indoles using (NH4)2S2O8 in dichloroethane at 80 °C. The efficiency of this catalytic approach was established by a broad scope of substrates involving quinones and hydroquinones to give high yields (61–93%) of 3-indolylquinones. The present protocol is simple, practical, and show good functional group tolerance. In addition, the obtained 3-indolylnaphthoquinones were conducted to further transformation to synthesize 2-amino-3-indolylnaphthoquinone and polycyclic N-heterocycles, respectively.
Keywords: quinones/hydroquinones; indoles; C–C coupling; 3-indolylquinones; (NH4)2S2O8-promoted